2015
DOI: 10.1039/c5cp00364d
|View full text |Cite
|
Sign up to set email alerts
|

Tuning magnetism by biaxial strain in native ZnO

Abstract: Magnetic ZnO, one of the most important diluted magnetic semiconductors (DMS), has attracted great scientific interest because of its possible technological applications in optomagnetic devices. Magnetism in this material is usually delicately tuned by the doping level, dislocations, and local structures. The rational control of magnetism in ZnO is a highly attractive approach for practical applications. Here, the tuning effect of biaxial strain on the d(0) magnetism of native imperfect ZnO is demonstrated thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 47 publications
3
8
0
Order By: Relevance
“…Based on previous results it is found that, ZnO NP may have very nominal magnetic moment which arises due to the intrinsic defects like surface OV . As discussed in the earlier section, the calculated small magnetic moment obtained for ZnO NP is seen to increase for halide attached NP due to increased electron affinity of attached halide ions and the resulting p‐d hybridization . Experimentally obtained per ion magnetic moments matches closely to the theoretical values as can be seen from Table .…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…Based on previous results it is found that, ZnO NP may have very nominal magnetic moment which arises due to the intrinsic defects like surface OV . As discussed in the earlier section, the calculated small magnetic moment obtained for ZnO NP is seen to increase for halide attached NP due to increased electron affinity of attached halide ions and the resulting p‐d hybridization . Experimentally obtained per ion magnetic moments matches closely to the theoretical values as can be seen from Table .…”
Section: Resultssupporting
confidence: 79%
“…Subsequently, in ZnO, ferromagnetic ordering has been found to exist in both undoped ZnO NP and also doped with magnetic and non‐magnetic ions. Based on previous results it is found that, ZnO NP may have very nominal magnetic moment which arises due to the intrinsic defects like surface OV . As discussed in the earlier section, the calculated small magnetic moment obtained for ZnO NP is seen to increase for halide attached NP due to increased electron affinity of attached halide ions and the resulting p‐d hybridization .…”
Section: Resultsmentioning
confidence: 64%
“…In particular, the changes in E form are about 0.12 and 0.34 eV in the case of 4% compressive strain, for V Zn and ( V Zn H), respectively. Similar variations in the formation energy for V Zn were observed in refs and . In particular, ref demonstrated for the first time that E form of zinc vacancy does not depend linearly on the strain due to the large structural relaxation around the vacancy.…”
Section: Resultssupporting
confidence: 80%
“…Ferromagnetism in undoped ZnO has been shown to originate from Zn vacancies (V Zn ) both from experiments ,, and DFT studies, ,, however we find that in order to explain the ferromagnetism measured in our experiments, a large concentration of vacancies would be required. Assuming that the ferromagnetism in ZnO originates from V Zn , each V Zn in the bulk is expected to contribute 2 μ B to the total magnetization based on our present DFT calculations (see Supporting Information for more details).…”
mentioning
confidence: 60%
“…Point defects, such as vacancies or interstitials, are an essential factor that determine the physical properties of materials. , The ability to control and manipulate point defects in materials synthesis and processing has been a fundamental strategy to achieve numerous desired optical, electrical, and magnetic functionalities . Nevertheless, the concentration of defects are usually restricted to relatively low levels by thermodynamics (e.g., due to high formation energy) or kinetics (e.g., due to slow growth rates). , Irregular defect types or high defect concentrations, though often predicted to enable exotic properties, are often associated with metastable states that are far from equilibrium. , For example, room-temperature ferromagnetism, discovered in ZnO due to the zinc vacancy (V Zn )-induced spin polarization of the top of the valence band, is intriguing for multiproperty coupling. However, the amplitude of ferromagnetism is generally very weak due to the limited V Zn concentration in the material lattice.…”
mentioning
confidence: 99%